A taxonomic reassessment of Caulerpa (Chlorophyta, Caulerpaceae) in southern Australia, based on tufA and rbcL sequence data. Issue 3 (4th May 2019) - Belton, Gareth S.; Draisma, Stefano G.A.; Prud'homme van Reine, Willem F.; Huisman, John M.; Gurgel, C. Frederico D.
ABSTRACT: Molecular characterisation (using tuf A and rbc L DNA sequences) of newly collected specimens of the genus Caulerpa in southern Australia identified 24 species and one variety, which, with the addition of four species and one variety recorded previously but not found during the present study, brings the total number of Caulerpa taxa in the region to 28 species and two varieties. Three new species are described based on molecular and morphological data: Caulerpa crispata comb . & stat. nov . (for C. longifolia f. crispata ), Caulerpa coppejansii sp. nov ., and Caulerpa perplexa sp. nov. Caulerpa coppejansii is a tropical West Pacific species and is included here due to its similarity to the southern Australian Caulerpa sedoides. Caulerpa perplexa is found in Western Australia and is a cryptic sister species of C. parvifolia Harvey from eastern Australia. The name Caulerpa muelleri is reinstated for C. flexilis var. muelleri . A new name, Caulerpa lucasii nom. nov ., is proposed for Caulerpa annulata Lucas nom. illeg ., a taxon shown to be distinct from Caulerpa hodgkinsoniae. Caulerpa corynephora and Caulerpa fergusonii are newly reported from the region, and a population of the potentially invasive Caulerpa cylindracea is reported from Portland, Victoria. An updated nomenclature is provided and reference tuf A sequences are proposed, as well as an updated identification key for southern Australian Caulerpa species.